From inclusive identities to inclusive societies: Global human identification and autonomy-oriented prosocial behavior regarding immigrants - Carmona, M.; Guerra, R. (XIII PhD Meeting in Social and Organizational Psychology, 2017)
Intergroup helping relations are also power/dependency relations between groups of unequal status, so helping behaviors can have ambivalent motivations and consequences. Considering the immigration context, this project aims to contribute, theoretically and empirically, to research on intergroup strategies, and underlying mechanisms, that promote autonomy-oriented prosocial behaviors from majority groups (i.e., host countries) regarding minority outgroups (i.e., immigrants). The novelty of this project relies on the analysis of the effects of different forms of inclusive identities on autonomy-oriented vs. dependency-oriented helping behaviors. Specifically, we aim to test whether a) complex social identities (i.e., global human identification) vs. common ingroup identities are more effective in promoting autonomy-oriented responses; b) if this effect is mediated by empathically motivated altruism; and, c) if specific intergroup conditions, namely threat perceptions and meta-perceptions about immigrants’ acculturation preferences, are seen as risk factors on the cost-benefit analysis of helping behavior.